You are on page 1of 5

# y2 - y1

x2 - x1
3-1
= 2
5-1 4

½
(1, 1)

y - y1 m(x - x1)

y - 1 ½(x - 1)

y - 1 = ½(x - 1)

y - 1 ½x - ½
+1 +1
y ½x + ½ 1

y = ½x + ½

Dec 21­6:36 PM

1
x1 y1 x2 y2 x1 y1 x2 y2

y2 - y1 -3 - -4 y2 - y1 = -3 - 6 = -9
m= = = 1 m= 8 - -4 12
x2 - x1 5-3 2 x2 - x1
m = -¾
y - y1 = m(x - x1)
y - y1 = m(x - x1)
y - -4 = ½(x - 3) y - 6 = -¾(x - -4)
y + 4 = ½x - 1½ y - 6 = -¾(x + 4)
-4 -4
y - 6 = -¾x - 3
y = ½x - 5 ½ +6 +6

y = -¾x + 3

Dec 21­6:25 PM

2
x1 x1 y1 x2 y2 x1 y1 x2 y2
y1 x2 y2

y2 - y1
m=
y2 - y1 1 - -6 m= = -3 - -9
= x2 - x1 6 - -2
x2 - x1 -2 - 5
6 3
7 m= =
m= = -1 8 4
-7

## y - y1 = m(x - x1) y - y1 = m(x - x1)

y - -6 = -1(x - 5) 3
y - -9 = (x - -2)
4
y + 6 = -1x + 5
3
-6 -6 y + 9 = (x + 2)
4
3
y = -1x - 1 y + 9 = x + 1½
4
-9 -9
3
y = x - 7½
4

Dec 21­6:26 PM

3
When given a slope and a point, you substitute them into the
point-slope form and simplify.
When given two points, you have to find the slope first. Then
substitute the slope and a point into the point-slope form.

Dec 21­7:03 PM

4
Assignment
Part I:    Pg. 282  #12­20 even, 24, 26

Part II:   Pg. 288  #22­32 even (do not graph), 52, 58

Dec 21­6:25 PM